FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN SISA MAKANAN PADA PASIEN KANKER PAYUDARA DI RUMAH SAKIT DADI KELUARGA PURWOKERTO - Triana Uji Pamungkas; Dyah Nur Subandriani (JURNAL RISET GIZI, 2017)
Background  : Visually observed in July - September 2016 the remaining food by 33%. While the results of visual observation of food residuals in breast cancer  patients  in January 2017 that is equal to 29.6%. This is not in accordance with the SPM is 20%. Objective  : To know the factors associated with the food of breast cancer patients at Dadi Keluarga Hospital Purwokerto. Methods  : The cross sectional study design was 38 samples. The data were obtained using questionnaires: appetite, psychic condition, food from outside hospital, family support, food appearance, food taste, and food residual form. The test used was chi square with α = 0, 05. Results  : The rest of the food was not eaten by patients 57.9%. Factors that influence the rest of the food include appetite 55,3%, normal psychic condition 60,5%, food from outside hospital 52,6%, family support 55,3%, appearance 55,3% and food taste 55,3% %. There was no association of feeding of breast cancer patients with appetite (p = 0,154), and psychic condition (p = 0,646). There was association of leftover food in breast cancer patients with food from outside hospital (p = 0,019), family support (p = 0,006), food appearance (p = 0,006), and food taste (p = 0,011). Conclusion  : The most associated factor with the remaining food of breast cancer patients is family support.